Numerical modelling and performance investigation of inorganic Copper-Tin-Sulfide (CTS) based perovskite solar cell with SCAPS-1D - Ayesha Siddique; Md. Nurul Islam; Hironmoy Karmaker; A.K.M. Asif Iqbal; Abdullah Al Mazed Khan; Md. Aminul Islam; Barun Kumar Das (Results in Optics, 2024)
Perovskite solar cells (PSCs) are a favorable option for the upcoming generation of photovoltaic systems due to their simplicity and high energy conversion efficiency. The third iteration of thin-film solar cells including copper-tin-sulphide (CTS) is easily accessible on Earth, possesses excellent optoelectrical properties, and does not include any harmful substances, making it environmentally sustainable. Using the solar cell capacitance simulator (SCAPS), this study examines the performance of a PSC based on copper oxide (Cu2O) and zinc selenide (ZnSe). The study investigates the factors that influence the performance of CTS-based SCs, such as absorber layer thickness, absorber defect density, interface defect densities, doping densities, and working temperature on the performance of the PSC. The results show that 30.37 % perovskite cell efficiency (PCE) increased from 20.94 % after optimization with 0.9403 V of open circuit voltage, 37.2682 mA/cm2 of short circuit current and 86.67 % of fill factor.